2013
DOI: 10.19173/irrodl.v14i3.1455
|View full text |Cite
|
Sign up to set email alerts
|

MOOCs: A systematic study of the published literature 2008-2012

Abstract: <p>Massive open online courses (MOOCs) are a recent addition to the range of online learning options. Since 2008, MOOCs have been run by a variety of public and elite universities, especially in North America. Many academics have taken interest in MOOCs recognising the potential to deliver education around the globe on an unprecedented scale; some of these academics are taking a research-oriented perspective and academic papers describing their research are starting to appear in the traditional media of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
459
1
37

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 843 publications
(501 citation statements)
references
References 34 publications
4
459
1
37
Order By: Relevance
“…For example, Perna et al (2014) studied learner usage in 16 MOOCs offered through Coursera, and found that fewer than half of registrants (46%) accessed one or more video lectures. Liyanagunawardena, Adams, and Williams (2013) examined 45 MOOC-related research papers published between 2008 and 2012, and noted that the highest rate of successful completion for any course was 19.2%, but the vast majority reported less than 10%. In addition, Jordan (2014) considered completion as the percentage of course registrants who met criteria to earn a course certificate in 39 MOOCs offered on different platforms (e.g., edX, Coursera, Udacity), and found a typical completion rate to be 5%.…”
Section: Learner Completionmentioning
confidence: 99%
“…For example, Perna et al (2014) studied learner usage in 16 MOOCs offered through Coursera, and found that fewer than half of registrants (46%) accessed one or more video lectures. Liyanagunawardena, Adams, and Williams (2013) examined 45 MOOC-related research papers published between 2008 and 2012, and noted that the highest rate of successful completion for any course was 19.2%, but the vast majority reported less than 10%. In addition, Jordan (2014) considered completion as the percentage of course registrants who met criteria to earn a course certificate in 39 MOOCs offered on different platforms (e.g., edX, Coursera, Udacity), and found a typical completion rate to be 5%.…”
Section: Learner Completionmentioning
confidence: 99%
“…For some researchers, the distinction between cMOOC and xMOOC is not so clear and there is still a gap in the literature in defining the types of MOOCs [15]. On the contrary, others maintain that 'they are so distinct in pedagogy that it is confusing to designate them by the same term' [12,16].…”
Section: Individualistic Vs Connectivist Moocsmentioning
confidence: 99%
“…Therefore, there should be a trade-off between having enough participants for an active forum and having too much participation which makes participants feel overwhelmed [32]. Large volumes of data generated in forums make it difficult and challenging to be up-to-date with the content [15].…”
Section: Individualistic Vs Connectivist Moocsmentioning
confidence: 99%
“…Three MOOC platforms are leading the race, Coursera, Udacity and EdX, and all three are associated with the highest ranking US universities. Generally MOOCs have no fees, prerequisite qualifications, formal accreditation or predefined levels of participation (Liyanagunawardena et al, 2013). Taking part is voluntary and depends on the interest and motivation of the learner.…”
Section: Introduction: Background To Moocsmentioning
confidence: 99%